O Discurso do Sujeito Coletivo sobre os Direitos Humanos dos Alunos da Educação de Jovens e Adultos na Cidade de Ponta Grossa/PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This dissertation aims to understand the Discourse of Collective Subjects (DCS) of the students of Education of Young and Adults of primary and secondary education on Human Rights above the theory of Social Representations (SR). For the accomplishment of this research, two Educational Centers of Basic Education for Young and Adult - CEEBJA of the city of Ponta Grossa / PR, with sixteen regular students of the high school of the morning period, twelve students of the primary school of the nocturnal period and two teachers volunteers, responsible for their respective classes. With a qualitative approach, the same developed by the character of participant research from the point of view of RS and DSC theory. The field diary, participant observation and questionnaire with open and closed questions For the analyze of the identified categories, it was used the discourse analysis of the collective subject and the Iramuteq software guided by the readings of Paulo Freire (1987, 1999, 2001a, 2001b and 2006) and Santos (2010, 2014), Arroyo (2017), Lefevre and Lefevre (2012, 2014) and Moscovici (1978, 2007). In order to understand the students' DSC about Human Rights, it is necessary to understand that the medium can interfere with the understanding of society on a certain subject, apprehended by the sum of its daily life, its experiences in the world of life to social relationships both within the school, and in their community and their means of access to information. In this way, it was possible to understand that human rights for students are expressed by stereotypes shaped by both the school and the media, such as: helping the needy and the prisoners, a right for "the other." These stereotypes are strengthened to the point that students who see themselves as itinerant workers who had their fundamental right denied and withdrawn during childhood and who, because of these, are forced to return to school to attain the minimum of human dignity by the search of the the labor market demands them. Also, through the research, it is emphasized that social representations are dynamic and can undergo changes throughout the research, mainly with the use of practices to work both the social representations and the information to the participants of the research. Finally, it is possible to emphasize that through restorative practices based on EDH, Humanistic Education of Paulo Freire, Restorative Justice and Education for Peace, it was possible to foster students' reflective process regarding their rights and the importance of Human Rights, such as a right of all humans, which needs to be strengthened daily for the creation of a Culture of Human Rights, Human Dignity and Peace.
Keywords: Cultura de Paz; Educação de jovens e adultos; Educação em Direitos Humanos; Práticas restaurativas; Educação humanizadora; Education in Human Rights; Restorative practices; Youth and Adult Education; Culture of Peace; Restorative Justice; Humanizing Education; CNPQ::CIENCIAS SOCIAIS APLICADAS